Exploring when and how adolescents sit: cross-sectional analysis of activPAL-measured patterns of daily sitting time, bouts and breaks - Lauren Arundell; Jo Salmon; Harriet Koorts; Ana Maria Contardo Ayala; Anna Timperio (BMC, 2019)
Abstract Background This study describes patterns of adolescents' objectively-measured sitting volume, sitting bouts, and breaks in sitting during different days and periods of the day, and explored differences by sex and weekdays versus weekend days. Methods ActivPAL™ data were collected in August 2014-December 2015 from adolescents attending secondary government schools in Melbourne Australia. Eight periods (early morning, mid-morning, morning break, late morning, lunch, early afternoon, late-afternoon and evening) were extracted for each day. School time, class time and out-of-school time were also extracted for weekdays. The percentage of time sitting, percentage of each hour in prolonged sitting (sitting bout ≥10 min), and number of sitting breaks/hour were calculated for each period. Differences by sex, and week and weekend days were determined using t-tests. Results Participants (n = 297, 15.4 ± 1.6 years) spent 68% of their day sitting; ~ 30% of each hour in prolonged sitting and 3.1 sitting breaks/hour. Sitting time was greater during class time (75%) and school (70%) compared to out-of-school time (65%). Sitting patterns differed between week and weekend days for all periods except the evening period. Girls had higher proportion of sitting during class than boys (76% vs 72% respectively) and school hours (72% vs 67%), more prolonged sitting during school hours (27% vs 23%), and more sitting breaks per hour during out-of-school time (2.6 vs 2.4), but fewer during class (2.5 vs 3.3) and school hours (2.7 vs 3.3). Sitting patterns did not differ by sex on weekend days. Conclusions Adolescents spent two-thirds of their waking hours sitting, with distinct patterns on weekdays and weekend days. Even though boys and girls were exposed to the same school day routine, girls spent more time sitting and had fewer sitting breaks. Class times, school breaks and the evening period were identified as key intervention periods. Further research is needed to understand the behavioural differences, and guide future intervention design.